Franz J. Hinkelammert: La opción político-cultural por los empobrecidos y el deseo de Dios - Gallardo, Helio (2022)
This article starts from the fact that, currently, religiosities and religious institutions have a determining political impact in certain situations. Hinkelammert’s approach is taken up according to which the emancipatory political decisions offered by religious and nonreligious referents in Latin America contain serious mystifications, the idea of Man being the main of them. It argues that, instead of these mystifications, one should look at the social sectors, whose existence is guaranteed, seeking the option for the impoverished, as a sociohistorical option.